Work, care and creativity in a time of COVID-19: creatively mapping presence bleed in the home. Issue 3 (3rd July 2022) - Hjorth, Larissa; Coombs, Gretchen; Hussey-Smith, Kelly; van Loon, Julienne
ABSTRACT: The pandemic restrictions and lockdowns have seen working from home (WFH) becoming a mundane practice. During the lockdowns, all movement were situated in the rhythms of the domestic and its infinite regresses of 'presence bleed' (Gregg [2011]. Work's Intimacy . London: Polity.) – informal care of older parents and young children, the gendered nature of care work and its often invisible role as it convergences with uneven expectations around working from home (WFH) and home schooling. In June 2020 we developed an open call for responses to the Work, Care and Creativity Study (WCCS). The study sought to explore the lived experiences of primary carers who are also creative professionals working and caring from home (WCFH) during the COVID-19 pandemic. Deploying creative practice techniques which use prompts (such as photos, drawing and creative writing responses) to elicit participant's experiences and emotions, this study sought to render visible some of the overlooked experiences, perceptions and practices emerging over the pandemic.